ANALISIS YURIDIS PENGUASAAN TANAH DENGAN MELAWAN HUKUM OLEH SEORANG YANG MENGAKU SEBAGAI AHLI WARIS (STUDI PUTUSAN PENGADILAN NEGERI NO. 51/PDT.G/2015/PN.LBp DAN PUTUSAN PENGADILAN TINGGI MEDAN NO. 220/PDT/2016/PT.MDN) - PATRICIA KACARIBU (Ilmu Hukum Prima (IHP), 2020)
Land plays a vital role in human life as land and human are inseparable one to another. Human beings live on land (reside) and acquire food by making use of land. Furthermore, land is also emotionally related to human. Everbody does not only need lan when they are alive, but they also need it when they die as a place to rest for good. The research problems are how about the mechanism of transfer of ownership rights over inherited land based on the Civil Law and Islamic Laws, how about the legak protection for heirs’ position in a dispute over ownership rights over inherited land in litigation process at court, and how about the analysis of the case in Lubuk Pakam Distric Court No. 51/Pdt.G/2015/PN.Lbp in conjunction with medan High Court No. 220/PDT/2016/PT.MDN. This is a normative juridical research which studies the prevailing laws and regulations such as the Civil Code, Ruling of Determination of heirs No. 27/Pdt.p/2006/PA-Lpk, Lubuk Pakam District Court Ruling Court No. 51/Pdt.G/2015/PN.Lbp in conjunction with medan High Court No. 220/PDT/2016/PT.MDN. this research problems to draw conclusions as the solution to problems. The results demonstrate that transfer ownership rights over inherited land in the civil laws is implemented by classifying heirs in accordance with inheritance system. Once the classification is established, it is possible to determine whome are rightful for the inheritance. In case of any dispute over the status of the valid heirs at court, the legal certainty is provided by Arcticle 171 of Civil Code which states that inheritance law is the law that regulates the transfer of ownership rights over a testator’s property, determines whom are rightful to be heirs, and to determine each person’s part. Tuhs, it is obvious that inheritance law refers to the civil law which explains that every person is rightful to become heors of a legal subject as a testator who are legally related in accordance with family law, that the testator and heirs actually have true and real close relationship.